Acute and delayed effects of sexual activity on athletic performance: A scoping review across sex, age, and ethnicity - Dhahbi, W.; Briki, W.; Dergaa, I.; Slim, I.; Omri, A. E.; Pyne, D. B.; Saad, H. B. (International Journal of Sports Physiology and Performance, 2026)
Purpose: The effects of sexual activity on athletic performance have been debated for centuries, with traditional abstinence beliefs lacking scientific foundation. We sought to map existing literature examining acute and delayed effects of sexual activity on athletic performance, and identify knowledge gaps across mechanistic pathways.